2022
DOI: 10.3390/jcm11144049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cardiovascular Risk Factors after Hepatitis C Virus Eradication with Direct-Acting Antivirals in a Cohort of Treatment-Naïve Patients without History of Cardiovascular Disease

Abstract: Background: Hepatitis C virus (HCV) produces changes at multiple levels in host metabolism, especially in lipid profile and cardio-metabolic risk. It is unclear how HCV eradication by direct-acting antivirals (DAAs) modifies those changes. Objective: To evaluate the impact of DAA treatment on different risk factors associated with cardiovascular disease. Methods: Prospective study with two-year follow-up. All patients treated with DAAs in the Liver Clinic of a tertiary hospital were included. Patients co-infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Among the studies that showed an increase in HDL, it appears to be consistent after the viral eradication, whereas during treatment HDL declined 13,91,96 . Higher baseline fibrosis, female sex, and the presence of metabolic syndrome seem to be the factors related to the increase in HDL after SVR 22,45,46,64,72,95 . On the other hand, a low fibrosis stage was associated with a reduction in HDL 61 .…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Among the studies that showed an increase in HDL, it appears to be consistent after the viral eradication, whereas during treatment HDL declined 13,91,96 . Higher baseline fibrosis, female sex, and the presence of metabolic syndrome seem to be the factors related to the increase in HDL after SVR 22,45,46,64,72,95 . On the other hand, a low fibrosis stage was associated with a reduction in HDL 61 .…”
Section: Resultsmentioning
confidence: 90%
“…While the majority of studies did not evidence a significant change in TGs levels after SVR, in longer follow‐up studies TGs seem to be higher after 2 years from SVR compared to baseline, 37,58 especially in male patients 64 . Moreover, TGs seem to increase later compared to TC and LDL 104 …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Our results describe how HCV-dependent lipid abnormalities are associated with insulin resistance and how DAA therapy can reverse this association. These findings suggest that monitoring the HDL-TG profile could predict changes in glucose tolerance and insulin resistance post-HCV clearance [ 78 ].…”
Section: Metabolic Changes Related To Treatment With Direct-acting An...mentioning
confidence: 99%